Analyzing University entrance exam physics questions using physics problems taxonomy for cognitive processes - SÜZÜK, EROL (My University, 2023)
University students often find physics challenging due to physical and mathematical obstacles, poor mathematical skills, and inadequate problemsolving abilities. This perception affects their interest and performance in the subject. High school students also struggle with numerical problems and understand curricular topics that lack concrete examples and require mathematical manipulations or visualization. Analyzing physics problems is crucial for guiding curriculum development, contributing to physics education, identifying students' difficulties in understanding and solving problems, and improving the process of physics education at all educational levels. Taxonomies are hierarchical frameworks used in education to classify educational learning goals or objectives according to their complexity. Bloom's Taxonomy, Anderson and Krathwohl's revised taxonomy, Lee Shulman's learning grid, Marzano's New Taxonomy of Educational Objectives (NTEO), and the Taxonomy of Introductory Physics Problems (TIPP) are all essential tools for understanding and improving educational learning outcomes. The study adapted the TIPP taxonomy into Turkish and analyzed 7 physics questions in the 2023 BPT. Results showed 3 questions were at recall, 1 at comprehension, and 3 at analysis, with no question at using knowledge. The study demonstrates that TIPP is a useful taxonomy for teachers to plan, apply, and evaluate knowledge and algorithms in solving physics problems, identifying students' needs. This taxonomy allows educators to create questions that engage students at all cognitive levels, promoting cognitive engagement. Researchers can analyze physics questions in the TYT and AYT in earlier years.
Keywords: Physics problems; basic proficiency test; taxonomy; cognitive processes